2020
DOI: 10.1212/wnl.0000000000009829
|View full text |Cite
|
Sign up to set email alerts
|

Generalized myoclonus in COVID-19

Abstract: ObjectiveTo report 3 patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) who developed generalized myoclonus.MethodsPatient data were obtained from medical records from the University Hospital “12 de Octubre,” Madrid, Spain.ResultsThree patients (2 men and 1 woman, aged 63–88 years) presented with mild hypersomnia and generalized myoclonus following the onset of the so-called inflammatory phase of coronavirus disease 2019 (COVID-19). All of them had presented previously with ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
137
3
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(163 citation statements)
references
References 19 publications
6
137
3
14
Order By: Relevance
“…Interestingly, cytokine-mediated neuroinflammation induced by SARS-CoV-2 has been implicated in steroid-responsive COVID-19-associated encephalopathy. 8 In addition to marked agitation in our patient, previous reports also had clinical/instrumental findings suggestive of encephalopathy, including dysexecutive syndrome, delirium, somnolence, EEG slowing, elevated inflammatory markers, variable responses to immunotherapies, and a benign clinical course, [1][2][3][4] further suggesting an immune-mediated/inflammatory pathogenesis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Interestingly, cytokine-mediated neuroinflammation induced by SARS-CoV-2 has been implicated in steroid-responsive COVID-19-associated encephalopathy. 8 In addition to marked agitation in our patient, previous reports also had clinical/instrumental findings suggestive of encephalopathy, including dysexecutive syndrome, delirium, somnolence, EEG slowing, elevated inflammatory markers, variable responses to immunotherapies, and a benign clinical course, [1][2][3][4] further suggesting an immune-mediated/inflammatory pathogenesis.…”
Section: Discussionsupporting
confidence: 60%
“…In previously published reports, myoclonus has been described as spontaneous or action-induced, multifocal or generalized, with a nonspecific distribution. [1][2][3][4] In our patient, the prominent involvement of axial and proximal limb muscles, myoclonus stimulus sensitivity, the absence of cortical discharges at EEG jerk-locked back-averaging, and the long duration of myoclonic bursts are consistent with subcortical myoclonus, possibly secondary to brainstem involvement.…”
Section: Discussionsupporting
confidence: 56%
“…A significant number of those diagnosed with COVID-19 have reported a broad spectrum of neurological consequences [26][27][28][29][30][31][32] . Neurological symptoms include those associated with dysfunction of the central (fatigue, headache, confusion, stroke 33 , dizziness, syncope 34 , seizure, anorexia, and insomnia) [35][36][37][38] , peripheral (anosmia, ageusia, myoclonus 39 , neuropathic pain, and myalgias) 26,35,40 , combined central-peripheral (Guillain Barre syndrome 41 ) and enteric nervous systems (diarrhea 13 ). Some gastrointestinal manifestations, including diarrhea, may be related to the expression of the viral receptor ACE2 and a serine protease, transmembrane serine protease 2 (TMPRSS2), involved in S protein priming, in the small intestinal epithelia and colon 42 .…”
Section: Symptomsmentioning
confidence: 99%
“…Physicians are seeing increasingly more patients with a spectrum of neurological manifestations associated with coronavirus disease 2019 (Ghosh et al 2020;Gutiérrez-Ortiz et al 2020;Rábano-Suárez et al 2020;Roy et al 2020). However, the pathogenesis of COVID-19-induced neurological manifestations is still in its infancy.…”
mentioning
confidence: 99%
“…Discussion SARS-CoV-2 has potential for neurotropism (Li et al 2020;Rábano-Suárez et al 2020;Roy et al 2020). Study with animal models have demonstrated that SARS-CoV and MERS-CoV, possibly via olfactory nerves, can spread rapidly inside central nervous system, thalamus and brainstem in particular (Li et al 2020).…”
mentioning
confidence: 99%